EXPERIENTIAL MARKETING TERHADAP CUSTOMER VALUE DAN CITRA SERTA PEMBELIAN ULANG - Rusna Purnama (Faculty of Economic and Business, University of Pasundan, 2020)
This study aims to determine the effect of experiential marketing on customer value and corporate image as well as its implications on the repurchase interest of cafe & restaurant visitors in Bandung. The research method used is descriptive and verification analysis. Data collection used was interviews using a questionnaire accompanied by observation and literature techniques, sampling techniques using consecutive sampling with a sample of 100 respondents. Data collection in the field was carried out in 2019. Data analysis techniques used Path Analysis. The results show that in general experiential marketing falls into the good category as well as customer value while the image and interest in repurchase tend to be sufficient. Experiential marketing influences customer value and company image and customer value and company image influences repurchase interest